Analytic And Iterative Reconstruction Algorithms In Myocardial Perfusion Spect: A Comparative Study - Mansor, Mohd Syahir (2012)

(untitled)
The purpose of this study was to compare the quality of images reconstructed using analytic or more commonly known as filtered back-projection (FBP) and iterative method based on maximum-likelihood expectation maximization (ML-EM) in myocardial perfusion (MP) single photon emmision computed tomography (SPECT). Phantom studies using different ratios of background activity to target activity (BTR) of 0.2, 0.4, 0.6 and 0.8 were used to simulate the different ratios of the activity in the lung to the activity in the heart (LHR) for patients undergoing MP SPECT.